Erratum: New Brunswick Endomychidae (Coleoptera) - Majka, Christopher G. (Zootaxa, 2009)
Majka (2007) newly recorded the endomychid beetle, Rhanidea unicolor (Ziegler, 1845), for the province of New Brunswick, Canada on the basis of a specimen collected in Charters Settlement, York County on 15 June 2002 by R.P. Webster.